The Exocyst Protein Sec10 Interacts with Polycystin-2 and Knockdown Causes PKD-Phenotypes - Fogelgren, Ben (Public Library of Science, 2011)
Autosomal dominant polycystic kidney disease (ADPKD) is characterized by formation of renal cysts that destroy the kidney. Mutations in PKD1 and PKD2, encoding polycystins-1 and -2, cause ADPKD. Polycystins are thought to function in primary cilia, but it is not well understood how these and other proteins are targeted to cilia. Here, we provide the first genetic and biochemical link between polycystins and the exocyst, a highly-conserved eight-protein membrane trafficking complex. We show that knockdown of exocyst component Sec10 yields cellular phenotypes associated with ADPKD, including loss of flow-generated calcium increases, hyperproliferation, and abnormal activation of MAPK. Sec10 knockdown in zebrafish phenocopies many aspects of polycystin-2 knockdown—including curly tail up, left-right patterning defects, glomerular expansion, and MAPK activation—suggesting that the exocyst is required for pkd2 function in vivo. We observe a synergistic genetic interaction between zebrafish sec10 and pkd2 for many of these cilia-related phenotypes. Importantly, we demonstrate a biochemical interaction between Sec10 and the ciliary proteins polycystin-2, IFT88, and IFT20 and co-localization of the exocyst and polycystin-2 at the primary cilium. Our work supports a model in which the exocyst is required for the ciliary localization of polycystin-2, thus allowing for polycystin-2 function in cellular processes.